ADAPTIVE SYNERGETIC AND LONG-RANGE COMMUNICATION LORA FOR QUADROTOR CONTROL AND INDOOR LOCALIZATION VIA INTERVAL ANALYSIS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
In this article, a new approach based on the use of received signal strength indication (RSSI) combined with long-range (LoRa) communication technology has been developed to locate a drone. Additionally, an interval analysis was introduced to enhance localization accuracy and system reliability. This approach involves taking into account several RSSI measurements over defined time intervals.  The quadrotor is controlled by an adaptive control system based on the passivity of the system’s ASC. By combining RSSI with LoRa technology, interval analysis, and passivity-based ASC control, our approach offers a robust and efficient solution for UAV control and localization. This methodology could be applied in a multitude of real-life scenarios, offering significant benefits in terms of safety, operational efficiency, and overall performance of UAV systems.
Keywords: New approach based on the use of RSSI (Received Signal Strength Indication) combined with LoRa (Long Range) communication technology has been developed to locate a drone